Information processing and anticipation in elite handball players: from the beginning to the top level - Biscaia, P.; Coelho, E.; Hernández-Mendo, A.; Alves, J. (Revista Iberoamericana de Psicologia del Ejercicio y el Deporte, 2018)
The aim of this study was to identify the difference between handball players starting level with high-level players terms of information processing and accuracy in anticipation, taking into account the competitive level and the amount of practice. The sample consisted of 71 female players of the national teams of handball Portugal. The ages were between 11 and 29 years old. The years of practice are between 1 and 18. The polyreaciometer for Windows (PRWin) was used to evaluate the processing of information. A protocol for collecting accuracy in anticipation using the paradigm of temporary occlusion (PROTANDE) was used.. For comparison of age groups MANOVA analysis, post hoc Tukey HSD and to correlate the variables the Pearson correlation coefficient was used was performed. The results suggest that the reaction time decreases in the levels / ages studied and levels players / age, of age have better reaction times and are more accurate in anticipation. Also the amount of practice leads to a decrease in processing time information, particularly in more complex situations. In conclusion, older players and more experienced process information more effectively and can anticipate more accurately.